Providing a knowledge audit model for Iranian startups - Ghasem Eslami; Mohammad Mehraeen; Mohammad Fadaei Khorasgani (مدیریت راهبردی دانش سازمانی)
The recent economic developments have led to fundamental changes in the business landscape, especially in terms of the level of competition for emerging enterprises, pushing them towards instability and failure. In response to this unstable environment, entrepreneurial businesses have evolved based on knowledge-centric ideas, seeking to address market gaps through the discovery of a replicable and scalable business model. Due to the knowledge-centric nature of these businesses, they consciously or unconsciously implement aspects of knowledge management processes, necessitating the identification and organization of their knowledge capital as a crucial first step. In this context, this study aims to explore a model for knowledge differentiation in Iranian entrepreneurial companies. The study adopts a developmental objective, an exploratory approach, interpretivism philosophy, and utilizes qualitative content analysis as its analytical strategy. The study population consists of experts in the field of knowledge management and active individuals in Iranian entrepreneurial companies. These individuals, familiar with the working conditions of these companies, expressed their opinions on the research topic through semi-structured interviews. The interview process began and continued until theoretical saturation was achieved. Participants were purposefully selected using the targeted sampling method, and after conducting 10 interviews, data saturation was reached. Following the interviews, the results were implemented, and descriptive content analysis using the maxqda software was employed. After content analysis, 41 different dimensions were extracted. Upon theoretical examination, appropriate names for the extracted dimensions were selected. The researcher, relying on prior knowledge and modeling processes from similar models, categorized the dimensions into 9 main processes of knowledge differentiation. By creating a logical sequence, the researcher innovatively devised a knowledge differentiation process model for Iranian entrepreneurial companies.